CASE STUDY MENURUNKAN STRES KERJA PERAWAT DENGAN TERAPI SELF HEALING MELALUI METODEEXPRESSIVE WRITING THERAPY DI RUANG MAHONI I RUMAH SAKIT BHAYANGKARA TK.I RADEN SAID SUKANTO - Muhammad Panji Asmoro (2022)
Stress is a physical and emotional response to the demands made on a person by his environment. The high work stress of nurses can affect the quality of nursing services. The results of observations made by the author in Mahogany Room I Bhayangkara Tk.I Hospital Raden Said Sukanto showed that from 14 nurses on duty there were 7 nurses (50%) who had mild stress, 5 nurses who had strong stress (35.7%) and 2 nurses (14.3%) who were included in the normal stress category. Based on these results, the authors applied evidence-based nursing in the form of self-healing therapy using the expressive writing therapy method on 5 nurses who had strong stress. Self-healing therapy using expressive writing therapy was carried out for 3 consecutive days with a duration of 20 minutes per session. The posttest results after applying self-healing therapy using the expressive writing therapy method showed that there were 1 nurse (20%) who was still in the category of strong stress and 3 nurses (80%) were included in the category of mild stress. This shows that the application of evidence-based self-healing therapy using expressive writing therapy has been proven to be able to overcome work stress on nurses. It is recommended that nurses can carry out this therapy when they are experiencing work stress.